MEMUNCULKAN KEMBALI SIYAR: HUKUM INTERNASIONAL ISLAM - Susetyo, Heru (UI Scholars Hub, 2021)
Islamic law is a complete and comprehensive law which encompassess all human affairs either in civil or public affairs. Islamic international law or siyar is a branch of Islamic law which regulate international affairs is among the topic which is frequently forgotten in Islamic discourse both in Indonesia or or other countries. Also in Indonesia where Islamic Law have been existing for centuries but mostly in civil affairs. This paper, therefore, would like to explore and discuss the siyar, as islamic international law from historical perspective, legal perspective and its relation to secular international law in regards to humanitarian law, law of diplomacy and other aspects of international public law. At the end, this paper emphasizes the need to promote and develop siyar as an integral part of Islamic law into national laws of possible Muslim countries.